1998
DOI: 10.21273/jashs.123.4.635
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Geographic Differentiation in Pawpaw [Asimina triloba (L.) Dunal] Populations from Nine States as Revealed by Allozyme Analysis

Abstract: As a new National Clonal Germplasm Repository for Asimina species at Kentucky State University (KSU), of major concern to us is the genetic variation within our germplasm collection. The present study investigated the extent of genetic diversity for the pawpaw germplasm in our collection and the geographical pattern of genetic diversity among populations using isozyme markers. Allozyme diversity was high in Asimina triloba (L.) Dunal (Annonaceae) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
6
15
0
Order By: Relevance
“…Partitioning of the population genetic diversity showed that genetic diversity within populations accounted for 81.3% of the total genetic diversity based on dominant AFLPs. This result agrees with fi ndings of Huang et al (1998Huang et al ( , 2000 using isozymes and RAPDs that most of the genetic diversity of pawpaw resides within the wild population. Furthermore, the proportion of 18.7% genetic diversity observed among A. triloba populations is slightly lower than the average for species with wide geographic range (21.0%), insect outcrossing species (24.3%), species with animal-ingested seed dispersal mechanisms (12.4% to 27.7%) and reproduction modes (21.3% to 22.5%), and temperate species (24.6%) (Hamrick and Godt, 1989).…”
Section: Inheritance Of Aflp Markers and Genetic Linkage Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…Partitioning of the population genetic diversity showed that genetic diversity within populations accounted for 81.3% of the total genetic diversity based on dominant AFLPs. This result agrees with fi ndings of Huang et al (1998Huang et al ( , 2000 using isozymes and RAPDs that most of the genetic diversity of pawpaw resides within the wild population. Furthermore, the proportion of 18.7% genetic diversity observed among A. triloba populations is slightly lower than the average for species with wide geographic range (21.0%), insect outcrossing species (24.3%), species with animal-ingested seed dispersal mechanisms (12.4% to 27.7%) and reproduction modes (21.3% to 22.5%), and temperate species (24.6%) (Hamrick and Godt, 1989).…”
Section: Inheritance Of Aflp Markers and Genetic Linkage Analysissupporting
confidence: 91%
“…Neiʼs genetic diversity (Nei, 1973) across all the populations was 0.077 (ranging from 0.039 to 0.074) estimated by dominant markers ( Table 2). The genetic diversity estimated using dominant AFLP markers among wild populations was lower than those estimated by RAPDs (0.249 for H e and 64% for percentage of polymorphic loci) (Huang et al, 2000) and isozymes (0.172 for H e and 43.5% for percentage of polymorphic loci) (Huang et al, 1998). The low level of H e estimated using dominant AFLP markers was due to the large portion (72%) of monomorphic markers.…”
Section: Inheritance Of Aflp Markers and Genetic Linkage Analysismentioning
confidence: 66%
See 1 more Smart Citation
“…In cherimoya (Annona cherimola), which is in the same family (Annonaceae), Escribano et al (2008) The development of superior pawpaw cultivars in terms of fruit quality and yield and the enhancement of genetic diversity contained in cultivars that are available to the public is crucial to the continued commercialization of pawpaw. High levels of genetic diversity exist in A. triloba (Huang et al, 1997(Huang et al, , 1998(Huang et al, , 2000Pomper et al, 2003Wang et al, 2005), which is consistent with frequent seed reproduction and adaptation of different environments. Grouping of genotypes in an unweighted pair group method with an arithmetic mean dendrogram showed that the PPF cultivars were more closely grouped with KSU advanced selections and that the older cultivars were genetically more distant than KSU or PPF selections unique genotypes.…”
Section: Discussionsupporting
confidence: 55%
“…A range of DNA and protein-based genetic marker systems has been used in attempts to evaluate genetic diversity in pawpaw. These marker systems include the minisatellite probe (Rogstad et al, 1991), allozymes (Huang et al, 1997(Huang et al, , 1998, random amplified polymorphic DNA [RAPD (Huang et al, 2000(Huang et al, , 2003], amplified fragment length polymorphism [AFLP (Wang et al, 2005)], intersimple sequence repeat [ISSR ], and SSR . Overall, these studies determined that the genetic variation in both cultivated and wild pawpaws is similar to those of other long-lived, temperate woody perennials characterized by a widespread geographic range, insect-pollinated outcrossing breeding systems, secondary asexual reproduction, and animal-dispersed seed.…”
mentioning
confidence: 99%